Fluoroquinolone-Induced Aortic Injury - N. V. Izmozherova; Artem A. Popov; V. M. Bakhtin; E. V. Markova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2021)
According to clinical studies, the use of ﬂuoroquinolone antibacterial agents is associated with such rare, but serious adverse reactions as aortic injuries. The aim of the study was to analyse scientiﬁc literature data on the risk of aortic injury during ﬂuoroquinolone treatment. The analytical review showed that the risk factors for ﬂuoroquinolone-induced aortic injury are male gender, age over 45 years, underlying aortic disease, as well as smoking and associated atherosclerosis. Clinical and morphological forms of ﬂuoroquinolone-associated aortic injuries include dilatation (aneurysm development), dissection, and rupture. The analysis of data on the association between aortic injuries and the use of most common ﬂuoroquinolones (ciproﬂoxacin, levoﬂoxacin, and moxiﬂoxacin) showed that development of aneurysm and dissection was most often observed for levoﬂoxacin, and least often for ciproﬂoxacin. The mechanism of aortic injury is due to ﬂuoroquinolone-mediated activation of matrix metalloproteinases which damage elastic components of vascular walls, as well as reduction in lysyl oxidase expression and collagen synthesis. The ability of ﬂuoroquinolones to form complexes with magnesium ions reduces the availability of magnesium to the cell enzyme systems, which delays synthesis of extracellular matrix structural proteins, leads to metalloproteinase activation and calciﬁcation of the vascular walls. Prevention, early detection, and timely management of the above-mentioned issues depend on the awareness of diﬀerent medical specialists about the risks of aortic injury associated with the use of ﬂuoroquinolone antibiotics.